The neuromuscular fatigue induced by repeated scrums generates instability that can be limited by appropriate recovery - Morel, B.; Hautier, C. A. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The aim of this study was to evaluate the influence of the fatigue on the machine scrum pushing sagittal forces during repeated scrums and to determine the origin of the knee extensor fatigue. Twelve elite U23 rugby union front row players performed six 6-s scrums every 30 s against a dynamic scrum machine with passive or active recovery. The peak, average, and the standard deviation of the force were measured. A neuromuscular testing procedure of the knee extensors was carried out before and immediately after the repeated scrum protocol including maximal voluntary force, evoked force, and voluntary activation. The average and peak forces did not decrease after six scrums with passive recovery. The standard deviation of the force increased by 70.2 ± 42.7% (P < 0.001). Maximal voluntary/evoked force and voluntary activation decreased (respectively 25.1 ± 7.0%, 14.6 ± 5.5%, and 24 ± 9.9%; P < 0.001). The standard deviation of the force did not increase with active recovery and was associated with lower decrease of maximal voluntary/evoked force and voluntary activation (respectively 12.8 ± 7.9%, 4.9 ± 6.5%, and 7.6 ± 4.1%; all P < 0.01). As a conclusion repeated scrummaging induced an increased machine scrum pushing instability associated with central and peripheral fatigue of the knee extensors. Active recovery seems to limit all these manifestations of fatigue.